Pengaruh Kualitas Produk dan Kualitas Layanan terhadap Loyalitas Pelanggan PT. Roman Ceramic International di Mojokerto: The Influence of Product Quality and Service Quality on Customer Loyalty of PT. Roman Ceramic International in Mojokerto - Prastyo, Habib Eko; Oetarjo, Mas (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2017)
This study aims to determine the effect of product quality and service quality to customer loyalty either partially or simultaneously, and to know the quality of product and service quality that has the most significant effect on customer loyalty at PT. Roman Ceramic International in Mojokerto. This research is done by quantitative method. The technique data used is questionnaires with a sample of 100 respondents. Data analysis technique used in this research is multiple linear regression using SPSS version 17 for windows. The results obtained based on the validity test show all existing questions are valid. This is done r count> r table. For reliability test can be concluded. The results of the research based on F test show the quality of the product and the quality simultaneous or together with customer loyalty. Test quality, product quality. Quality of service has the most significant influence on customer loyalty due to having the largest t arithmetic compared with product quality variables.